2018
DOI: 10.1016/j.jbiomech.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional temporomandibular joint muscle attachment morphometry and its impacts on musculoskeletal modeling

Abstract: In musculoskeletal models of the human temporomandibular joint (TMJ), muscles are typically represented by force vectors that connect approximate muscle origin and insertion centroids (centroid-to-centroid force vectors). This simplification assumes equivalent moment arms and muscle lengths for all fibers within a muscle even with complex geometry and may result in inaccurate estimations of muscle force and joint loading. The objectives of this study were to quantify the three-dimensional (3D) human TMJ muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…However, the insertion areas evaluated in the present study were 2.0 cm 2 and were therefore larger than those of the aforementioned study. Since the insertion area on the pterygoid fovea in the present study was 1.4 cm 2 and almost identical with the study of She et al (2018), the discrepancy might be explained by whether or not there was specific focus on the insertion area on the medial surface of the condylar process. On the basis of occupying one‐third of the total insertion area, we concluded that the lateral pterygoid had a broad insertion area on the medial surface of the condylar process which should not be ignored.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the insertion areas evaluated in the present study were 2.0 cm 2 and were therefore larger than those of the aforementioned study. Since the insertion area on the pterygoid fovea in the present study was 1.4 cm 2 and almost identical with the study of She et al (2018), the discrepancy might be explained by whether or not there was specific focus on the insertion area on the medial surface of the condylar process. On the basis of occupying one‐third of the total insertion area, we concluded that the lateral pterygoid had a broad insertion area on the medial surface of the condylar process which should not be ignored.…”
Section: Discussionsupporting
confidence: 81%
“…Data on the dimensions of the insertion area of the lateral pterygoid is limited in the literature. Recently, She et al (2018) reported that the total insertion area of the lateral pterygoid was 1.4 cm 2 based on the three‐dimensional cone‐beam CT images. However, the insertion areas evaluated in the present study were 2.0 cm 2 and were therefore larger than those of the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, during the act of narghile smoking, the mandible is found to be pulled forward (personal observation). Over activity of the jaw muscles causes excessive loading of the TMJ [34]. It had been reported that overloading of the TMJ tends to squeeze the intra-articular disc forward; and with repeated activity the disc becomes permanently displaced forward at rest, leading to internal derangement of the joint [35].…”
Section: Discussionmentioning
confidence: 99%